Light and photosynthesis in aquatic ecosystems - Kirk, John T. O. (John Thomas Osmond), 1935- (Cambridge ; Cambridge University Press, 2010)
'Beginning systematically with the fundamentals, the fully-updated third edition of this popular graduate textbook provides an understanding of all the essential elements of marine optics. It explains the key role of light as a major factor in determining the operation and biological composition of aquatic ecosystems, and its scope ranges from the physics of light transmission within water, through the biochemistry and physiology of aquatic photosynthesis, to the ecological relationships that depend on the underwater light climate. This book also provides a valuable introduction to the remote sensing of the ocean from space, which is now recognized to be of great environmental significance due to its direct relevance to global warming. An important resource for graduate courses on marine optics, aquatic photosynthesis, or ocean remote sensing; and for aquatic scientists, both oceanographers and limnologists'--
Machine generated contents note: Preface to the third edition; Part I. The Underwater Light Field: 1. Concepts of hydrologic optics; 2. Incident solar radiation; 3. Absorption of light within the aquatic medium; 4. Scattering of light within the aquatic medium; 5. Characterizing the underwater light field; 6. The nature of the underwater light field; 7. Remote sensing of the aquatic environment; Part II. Photosynthesis in the Aquatic Environment: 8. The photosynthetic apparatus of aquatic plants; 9. Light capture by aquatic plants; 10. Photosynthesis as a function of the incident light; 11. Photosynthesis in the aquatic environment; 12. Ecological strategies; References and author index; Index to symbols; Index to organisms; Index to water bodies; Subject index.
Includes bibliographical references and indexes.
Keywords: Photosynthesis; Plants -- Effect of underwater light on; Aquatic plants -- Ecophysiology; Underwater light